2018
DOI: 10.1111/cen.13557
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density and bone turnover markers during treatment with teriparatide in pregnancy‐ and lactation‐associated osteoporosis

Abstract: In patients with PLO, LSBMD at 12 months increased in both the TPTD-treated and control groups. TPTD treatment and younger age were associated with greater increases in LSMBD irrespective of baseline LSBMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 33 publications
(54 reference statements)
2
30
0
1
Order By: Relevance
“…Thus, the very low bone remodeling state in women with PLO may have implications for both our understanding of disease mechanisms, and our expectations for responsiveness to therapeutic agents that stimulate bone formation. In this regard, a relatively large study of teriparatide in 27 women with PLO found that teriparatide responsiveness was quite variable, with spine aBMD changes at 12 months ranging from 4.5% to 34.3% . Thus, some women with PLO may be relatively unresponsive to teriparatide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the very low bone remodeling state in women with PLO may have implications for both our understanding of disease mechanisms, and our expectations for responsiveness to therapeutic agents that stimulate bone formation. In this regard, a relatively large study of teriparatide in 27 women with PLO found that teriparatide responsiveness was quite variable, with spine aBMD changes at 12 months ranging from 4.5% to 34.3% . Thus, some women with PLO may be relatively unresponsive to teriparatide.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8) This assumption reflects data available from a great many studies of bone density and bone remodeling changes that occur with normal pregnancy, lactation, and weaning in healthy women. As in healthy women, studies of PLO women document large postpartum and postweaning BMD increases (45,48) ; however, it is not known whether PLO women experience the same trajectory of bone density and remodeling recovery as normal women. Thus, it is possible that some PLO women had further BMD increase after the study time point.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…W ostatnich latach u wielu kobiet z PLO stosowano terapię teryparatydem (rekombinowany ludzki 1-34 parathormon), wykorzystując jego anaboliczny wpływ na kości [4,20]. Wydaje się, że efekt jest lepszy niż w przypadku bisfosfonianów, poprawa kliniczna następuje dość szybko, a przyrost BMD sięga u niektórych chorych nawet 14-35% [20][21][22][23]. Kojarzono też teryparatyd z bisfosfonianem z dobrym efektem [1,4].…”
Section: Omówienieunclassified
“… 2 The typical clinical features of PLO are low back or hip pain and a decrease in self-awareness of height in the third trimester of pregnancy and postpartum. 3 Fragility fractures may occur in women with severe osteoporosis, and predominantly occur in the thoracolumbar spine. 4 The incidence of PLO is four in 1 million women and many of these patients are misdiagnosed.…”
Section: Introductionmentioning
confidence: 99%